Statistical analysis of fiber/matrix bond strength of hybrid Gengronema Latifolium stem/S-glass fibers reinforced epoxy composites - Christian Emeka Okafor; Peter Chukwuemeka Ugwu; Godspower Onyekachukwu Ekwueme; Chibuzo Ndubuisi Okoye; Augustine Uzodinma Madumere (Britain International for Academic Research (BIAR) Publisher, 2025)
The primary aim of the present study is to evaluate the effects of hybridization ratio, fiber orientation, and mass fraction on the fiber/matrix bond properties of hybrid Gongronema latifolium stem/S-glass fiber reinforced epoxy composites. Gongronema latifolium plant stem fibers were collected from Anambra State, Nigeria, with leaves removed manually. Sodium hydroxide (2%) and epoxy resin (Grade-3554A) were used, while S-Glass was sourced locally. The fibers were extracted using a water retting method, treated with NaOH at 40-60°C for 4 hours, and dried at 70°C. For composite fabrication, fibers were aligned unidirectionally and mixed with resin and S-glass in a 250×100×5 mm mold. The hybridization ratio of S-Glass to natural fiber was fixed at 2.2 for Level 1 and 2.8 for Level 2. The mass fraction levels were at 21.24% for level one and 34.22% for level two. Fiber orientation of Level 1 was 45° while that of Level 2 was 90°. Mechanical characteristics were evaluated to ASTM D5651-21 for fiber-matrix bond strength and then analyzed using Statistical Package for Social Sciences (SPSS) and Microsoft Excel. Three models were developed, with the first model considering hybridization ratio, the second incorporating fiber orientation, and the third including mass fraction. The results show that the hybridization ratio is the most significant predictor of bond strength, with fiber orientation and mass fraction also contributing positively to the overall model. Models’ R-square values indicated how well the proposed models fitted the data: Model 1 = 0.747; Model 2 = 0.956; Model 3 = 0.980. Two unique solutions were examined further at fiber/matrix bond strength value of 0.32716MPa and value of 0.18070MPa, with a mean value of 0.25393 MPa and standard deviation value of 0.10356 MPa. The study reveals the impact of these factors on enhancing the bond strength of the composite material. The research has important and real-world applications for industries including construction, automotive, aerospace, and others where stiffer and more resistant composites are required. Future studies could be directed to investigate other variables and environmental factors that may influence performance of these hybrid composites to improve on their applications.